Mores, fault and fides: are these acceptable criteria when income tax deductions are claimed - Swanepoel, Marius G (Rhodes University, Faculty of Commerce, Department of Accounting, 2007)
The two "pillars" on which taxable income is based are the definition of "gross income" in section 1 of the Income Tax Act, 58 of 1962, and the "general deduction formula" comprising the preamble to section 11, section 11(a) and section 23(g) of the Act. Many of the terms used in these sections are not defined in the Income Tax Act. Case law in relation to these sections reveals that morality issues, the negligence of taxpayers and the good faith of taxpayers have from time to time been treated as relevant considerations by the courts, both abroad and in South Africa, in allowing or disallowing deductions from the gross income of taxpayers. In some instances this occurred apparently unwittingly. In other instances, earlier decisions were followed without a thorough consideration of the correctness of the underlying reasoning or of the criteria which were applied in the earlier decisions. In relation to the definition of "gross income" , however, fides, mores and fault have not been a consideration. In CIR v Delagoa Bay Cigarette Co Ltd 1918 TPD 391 Bristowe, J stated: "I do not think it is material for the purpose of this case whether the business carried on by the company is legal or illegal." There were a number of cases heard in relation to income from illegal activities (for example, COT v G, 1981 (4) SA 167 (ZA), 43 SATC 159, and ITC 291, 7 SATC 335, which related to the misappropriation of funds, ITC 1545, 54 SATC 464, which dealt with the proceeds of the sale of stolen diamonds and ITC 1624, 59 SATC 373, which dealt with overcharging customers). In these cases, the question turned on whether or not the amounts were received by the taxpayers for their own benefit and therefore to be included in gross income, or whether the taxpayers incurred a concomitant liability to repay the amounts, and did not involve the question of fides, mores or fault. The research concludes that, providing an even-handed approach is applied to both income and expense considerations, fides and mores may continue to play a role as a useful yardstick in this context. However, that fault, particularly the causal negligence of taxpayers in the process of sustaining a loss or incurring expenditure whilst conducting their income generating operations, has effectively been jettisoned as an irrelevant consideration, is a salutary development which has contributed to legal certainty.
Keywords: Uncatalogued